The Combined Effect of Mediterranean Shrubland Pasture and the Dietary Administration of Sage By-Products on the Antioxidant Status of Segureña Ewes and Lambs - María J. Jordán; Cristina Martínez-Conesa; Sancho Bañón; Julio Otal; María Quílez; Inmaculada García-Aledo; Pascual Romero-Espinar; Pedro Sánchez-Gómez (MDPI AG, 2020)
The objective of this study was to determine if the combined effect of ewe grazing and the incorporation of sage by-products in the lamb feed enhances the Segureña ewe and lamb antioxidant status. For that, the endogenous (related to blood antioxidant enzymes) and exogenous (plasma antioxidant activity) antioxidant systems of ewes and lambs were studied at the physiological stages of lactation, after weaning and at the end of the fattening period. Major results indicated that grazing improved the enzymatic antioxidant defense of ewes during the stressful period of lamb weaning, and also, the antioxidant status of the ewe plasma at both physiological stages: lactation and after lamb weaning. With regards to the lambs, ewe grazing stimulated the antioxidant enzymatic defense during lactation, but not the antioxidant capacity of the plasma. At the end of the fattening period, the inclusion of sage by-products in the lamb diet (10% w/w) enhanced both the enzymatic cascade and antioxidant capacity of the lamb plasma. The antioxidant capacity of the lamb meat was also studied and the benefits of sage were detected in samples from the deltoideus muscle. Thus, Mediterranean grazing stimulated the antioxidant defense in ewes, while the inclusion of sage by-products in the lamb diets enhanced the antioxidant status of both blood and meat.